2010
DOI: 10.1111/j.1365-3083.2009.02367.x
|View full text |Cite
|
Sign up to set email alerts
|

LLT1‐mediated Activation of IFN‐γ Production in Human Natural Killer Cells Involves ERK Signalling Pathway

Abstract: Natural killer (NK) cell functions are regulated by a delicate balance of signals received through activating and inhibitory receptors expressed on the cell surface. Lectin‐like transcript‐1 (LLT1), expressed on a subpopulation of NK cells and other immune cells is a ligand for the NK cell inhibitory receptor, NKR‐P1A (CD161). Previous studies showed that cross‐linking surface LLT1 with a monoclonal antibody stimulated NK cell IFN‐γ secretion but had no effect on cytotoxicity. Here, we have examined the signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…18) and ILF3 (refs. 19, 20) are involved in the induction of ILC cytotoxic function, whereas HECT and RLD domain-containing E3 ubiquitin protein ligase 3 (HERC3) and MAP2K1 (ref. 21) are involved in enhancing the function of ILCs (i.e., classical and nonclassical MHC class I).…”
Section: Resultsmentioning
confidence: 99%
“…18) and ILF3 (refs. 19, 20) are involved in the induction of ILC cytotoxic function, whereas HECT and RLD domain-containing E3 ubiquitin protein ligase 3 (HERC3) and MAP2K1 (ref. 21) are involved in enhancing the function of ILCs (i.e., classical and nonclassical MHC class I).…”
Section: Resultsmentioning
confidence: 99%
“…This secretion was reduced in the presence of anti-CD161 antibody. The effect of CD161 triggering on NK or T cell effector activities is still controversial [19], [26]. A recent report suggests that CD161 has stimulatory function on IL-17 producing CD4 T cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while LLT1 inhibits cytotoxicity and IFN-γ production via NKR-P1A on NK cells, it appears to costimulate IFN-γ production by NKT cells (47, 107). Reciprocal studies have suggested that LLT1 itself may signal on NK and NKT cells to augment IFN-γ production via a Src-family–ERK signaling pathway (61, 152). …”
Section: Functionmentioning
confidence: 99%